The Dao of Muhammad: A Cultural History of Muslims in Late Imperial China by Zvi Ben-Dor Benite (Cambridge: Harvard University Press, 2005. 280 pages.) (American Journal of Islam and Society, 2006)
Zvi Ben-Dor Benite has contributed an important piece to the history ofMuslims in imperial China, centered on a seventeenth-century Muslimgenealogy known as the Jing Xue Xi Chuan Pu (hereinafter Genealogy),which has been recently discovered, punctuated, and printed as the Jing XueXi Chuan Pu (Xining: Qinghai Renmin Chubanshe, 1989). His book followsSachiko Murata’s study of Confucian Muslim texts and teachers (namely,Chinese Gleams of Sufi Light: Wang Tai-Yu’s Great Learning of Pure andReal and Liu Chih’s Displaying the Concealment of the Real Realm [Albany,NY: State University of New York, 2000]) and illuminates many aspects ofthe Muslims’ cultural life in imperial China.The book consists of an introduction, four chapters, and a conclusionwith tables and illustrations. The first chapter decodes the Genealogy andoutlines the trajectory of the Chinese Muslims’ educational network in centraland coastal China. The second chapter explores the “social logic”behind the practices of the Muslim literati (p. 74) – that is, how they envisionedand understood the educational system, their roles, and Islam in referenceto imperial China’s existing sociocultural categories. This chapterreveals how Muslim educational institutions enabled and empoweredMuslim intellectuals to convert “Islam” and “Muslim” into valid social categoriesof school (xuepai) and to envision themselves as “literati” (shi) thatwere as much Chinese as Muslim.The third chapter analyzes the transformation of Islamic knowledge from“orality” to “texuality” (p. 158) and the formation of the Chinese Islamicschool, which was patterned on contemporary Chinese schools of scholarship.The fourth chapter explains how Confucian Muslims interpreted Islam,Prophet Muhammad, and Islamic canons as equivalents and counterparts ofConfucianism (enumerated in the Han Kitab as “Dao,” “Sage,” and “Classic”),and how the Muslim literati embraced Confucianism. In the ...